AB0060 Modelling delayed bone healing in a mouse-osteotomy model to evaluate therapeutic strategies for affected patients with ra. (15th June 2017) - Lang, A; Fügener, S; Hoff, P; Schmidt-Bleek, K; Gaber, T; Buttgereit, F
Abstract : Background: Anti-inflammatory treatment of rheumatoid arthritis (RA) using non-steroidal anti-inflammatory drugs (NSAID) or glucocorticoids (GC) as well as the disease itself, are supposed to negatively influence bone metabolism and healing. However, in vivo models allowing to evaluate therapeutic strategies for patients suffering from delayed bone healing are scarce and mainly created by critical size defects that are not representative for comorbity-induced disorders. In addition, there are no adequate rodent models allowing the analyses of the influence on the bone metabolism by the complete dysregulation of the immune system in RA as well as long-term medications with NSAID or GC. Previously, we have shown that immunologically restricted patients lack an adequate adaptation to hypoxia in the fracture hematoma thus facilitating healing disorders (1). The hypoxic microenvironment during the initial fracture-healing phase is known to be essential for activating the immunological reactions, which induce the regeneration. Furthermore, we performed a single-center retrospective study on fracture healing disorders showing a significant high prevalence for RA patients to be affected by delayed bone healing. Objectives: In order to evaluate therapeutic strategies for affected patients with RA, we developed a model for delayed bone healing in a mouse-osteotomy model. Methods: Female C57BL aged 12 weeks underwent osteotomy of the femur (fracture gap 0, 7 mm) that was fixated with an external fixator (RIS-System). Lyostypt® (based on bovine Col I; mimicking extracellular bone matrix) was applied in the fracture gap and analysis was performed 2 and 3 weeks after surgery. The ratio of bone volume (BV) per total volume (TV) in the fracture gap was evaluated using in vitro μCT. In addition, Movat's pentachrome staining was performed to analyze the cellular and tissue composition within the fracture gap. To investigate the number of cells as well as the vessel formation, we used immunofluorescence to stain for Endomucin, PECAM-1 and DAPI. Quantitative analysis of histological staining was conducted by using ImageJ. Results: We developed an in vivo mouse-osteotomy model showing delayed bone healing by applying Lyostypt® in the fracture gap. The BV, TV as well as the ratio was significantly higher in the controls (empty gap = normal healing; n=8 per timepoint) as compared to the Lyostypt® group (n=8 per timepoint) 2 weeks after osteotomy and slightly higher after 3 weeks. Histological investigation showed the clear presence of the scaffold on both timepoints without briding cartilaginous tissue. The cell number as well as the vessel formation was significantly reduced within the fracture gap. Conclusions: The results obtained so far support the hypothesis that we were able to develop a delayed healing or even non-union osteotomy model in mice by avoiding to create a critical size defect. Therefore, this approach represents a promising alternative animal model to evaluate therapeutic strategies to overcome bone healing complications in RA patients and perhaps other immunologically restricted patients. References: Hoff et al. 2011 Immunol Res 51(1):116–22. Disclosure of Interest: None declared